Perencanaan perkerasan jalan raya pada perlintasan sebidang di JPL 136 Kota Madiun - Kurniawan, Muhammad Adib; Astuti, Septiana Widi; Dewi, Puspita; Puruhita, Hana Wardani; Riyanta, Wawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The construction of road pavements at level crossings typically employs flexible asphalt pavements, which are prone to peeling and damage. It has been stated that the pavement structure at at-grade crossings between roads and railway tracks should differ from the pavement structure in sections approaching the crossing. The pavement structure at at-grade crossings is recommended to have greater strength than the pavement structure on existing road sections, such as the use of rigid concrete pavements (Prasarana, 2004). In this research, the road pavement at the JPL 136 at-grade crossing in Madiun City is planned to use rigid cement concrete pavement, with the construction calculation using the cement concrete pavement planning method (Ministry of Public Works and Housing, 2003). After analysis, a rigid cement concrete pavement construction with a thickness of 150 mm, a compressive strength of 35 MPa, longitudinal reinforcement D16-170, and transverse reinforcement D12-100 with BJTS 420 A type was obtained.